Cartographie krigée des mollusques suspensivores compétiteurs trophiques des huîtres du bassin de Marennes-Oléron : l'implications pour la planification de l'échantillonnage - Sauriau, Pierre-guy; Bacher, Cedric (Institut océanographie, 1991)
Stock assessement of wild soft-bottom mol/uses has been part of a general approach to shellfish management in oyster farming in Marennes-Oleron Bay. A sampling survey is described as a stratified random sampling after optimum allocation of the sample sire in each stratum. The aim of this study is ta ilIustrate the use of kriging techniques in the case of suspension-feeders. Regarding suspension-feeding molluscs. trophic competitors of the oyster Crassostrea gigas the whole stratified design produced an estimation with a precision around 25%. Then the geostatistical technique. i.e. kriging was used to depict the spatial and variability patterns of several trophic groups. The biomass data are expressed in ash-free. dry-weight units. In addition, the characteristics of the spatial distribution of suspension feeders revealed by the kriging analysis. are compared to the initial features and results of the stratified plan L'estimation des stocks des peuplements benthiques du bassin de Marenens-Oléron s'inscrit dans un processus d'élaboration de modèles prévisionnels de gestion des cheptels conchylicoles. Focalisée sur les mollusques benthiques non cultivés, par opposition aux mollusques en élevage (Crassostrea gigas et Mytilus edulis), cette estimation s'est appuyée sur un échantillonnage aléatoire stratifié.